2017
DOI: 10.1038/ncomms15062
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose penicillin in early life induces long-term changes in murine gut microbiota, brain cytokines and behavior

Abstract: There is increasing concern about potential long-term effects of antibiotics on children's health. Epidemiological studies have revealed that early-life antibiotic exposure can increase the risk of developing immune and metabolic diseases, and rodent studies have shown that administration of high doses of antibiotics has long-term effects on brain neurochemistry and behaviour. Here we investigate whether low-dose penicillin in late pregnancy and early postnatal life induces long-term effects in the offspring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
252
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(274 citation statements)
references
References 76 publications
16
252
2
4
Order By: Relevance
“…In addition, treating animals with antibiotics to disrupt the microbiome led to changes in social behavior [49]. Stress during gestation alters the composition of the maternal microbiome and these changes are transmitted to the offspring [3,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treating animals with antibiotics to disrupt the microbiome led to changes in social behavior [49]. Stress during gestation alters the composition of the maternal microbiome and these changes are transmitted to the offspring [3,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…[90,96] Finally, different probiotic strains have been shown to reduce symptoms of anxiety and depression across several studies in clinical and healthy populations. [97,98] While there have also [5,9,10,88,90] Anxiolytic effects, sometimes sex-specific, in mice (light-dark box, elevated-plus maze) [72,113] Anxiolytic effects in mice (open field, defensive marble burying, elevated-plus maze, light-dark box) [91,93] Strain-specific anxiolytic effects in humans (e.g., Beck Anxiety Index, Hospital Anxiety & Depression Scale) and rodents (defensive marble burying, elevated-plus maze, open field) [11,62,133,134] Transplant from humans with depression or comorbid IBS and anxiety increases anxietylike behavior in mice (open field, step-down test, light-dark box) [96,125] Heightened anxiety in rats (open field) [89] Depression Increased depressive-like behavior in mice (forced swim) [90] Increased depressive-like behavior in rats (forced swim) [94] Antidepressant effects in mice and rats (forced swim, tail suspension, learned helplessness after inescapable shock) [91,92] Strain-specific antidepressant effects in humans (e.g. Beck Depression Inventory, Hospital Anxiety & Depression Scale) and rodents (tail suspension test, forced swim, sucrose preference) [11,97,98,133,134] Transplant from depressed human donors induces depressive-like behavior in mice (sucrose preference, forced swim [varied results], tail suspension test) [90,96] Learned fear Impaired fear recall in adult mice [101] Acute administration enhances fear extinction in rodents and exposure therapy in humans, [103,104] reduces fear recall in huma...…”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal clinical studies support the idea that early-life exposure to antibiotics perturbs the natural trajectory of the microbial communities by altering their stability [140]. Furthermore, neonatal exposure to antibiotics in rodents not only altered the microbiota but also induced increased visceral sensitivity and long-lasting changes in brain cytokines and behaviour [141, 142]. …”
Section: Early Postnatal Perturbations Of the Microbiotamentioning
confidence: 83%